Implementation of the Constitution, Federalism, Inclusion and Policies Related to International Relations - Gyawali, Chandra Kanta (NCWA Annual Journal, 2026)
The Constitution of Nepal has embraced federalism, inclusiveness, a parliamentary system of governance, and policies relating to international relations. The Constituent Assembly rejected the concept of a directly elected presidential and prime ministerial system. The distribution of power among the central, provincial, and local levels of government in the federal system is clearly set out in the constitution. Central, provincial, territorial, geographical, or local governments are various forms of federal governance. Although it is often described as having two governments, two administrations, and two legislatures, Nepal has three levels of government and administration and three levels of legislature and assembly. The nature of the judiciary in a federal system can be general and federal. In Nepal’s case, although the judiciary is unitary, the structure of the Constitutional Bench and the High Court is oriented toward a unified judiciary. Speaking of South Asia, the federal system of governance has been adopted especially in India, Pakistan, and Nepal. Other countries have a unitary system of government. Federalism, inclusion, and principles of non-alignment and Panchsheel are the basic features of Nepal’s constitution. This article aims to highlight the necessity for the implementation of federalism and inclusion, as well as the principle of non-alignment in its truest sense, in accordance with the Constitution of Nepal.